How can medical students suffering from hearing loss auscultate their patients? - Riva, Michele Augusto; Bava, Mattia; D'Orso, Marco Italo; De Vito, Giovanni; Cesana, Giancarlo (La Medicina del Lavoro, 2014)
Auscultation is a fundamental part of medical examination. It is generally performed using a stethoscope which allows listening to body sounds, in particular of the heart and lungs, the function of which can be initially explored using this instrument. According to Rabinowitz et al., despite improvements in diagnostic technology, “the ability to auscultate a patient’s heart and lungs using a stethoscope remains the basic occupational skill for physicians”...